PENERAPAN TERAPI BERMAIN PLASTISIN PADA AN. R (6 TAHUN) DENGAN DENGUE HAEMORAGIC FEVER AKIBAT HOSPITALISASI TERHADAP KECEMASAN SEDANG DI RUANG MELATI RS TK. II DUSTIRA CIMAHI - Nawal; Dewi Safariah, Triana (Yayasan Putra Sukamanah Sejahtera, 2024)
Dengue Haemoragic Fever (DHF) is an infectious disease caused by the dengue virus transmitted through the bite of the Aedes aegepty mosquito. Dengue Haemoragic Fever can cause complications namely dengue shock syndrome and cause death especially in children. Preschoolers with DHF often experience anxiety due to hospitalization, one of the treatments is play therapy, then an intervention is prescribed plasticine play therapy. Plasticine play therapy is playing night candles that are soft and easy to shape as desired with a variety of colors of choice and can play on the bed and can reduce anxiety. The purpose of this case study was to identify the level of anxiety before and after plasticine play therapy in preschool children (3-6 years) with dengue haemoragic fever due to hospitalization of moderate anxiety. Plasticine focuses on reducing anxiety in children and helps increase children's creativity. The method used is an analytical descriptive method in the form of a case study with a nursing process approach. The results of this study showed that children experienced anxiety, tension and fear, nursing actions were carried out so that the nursing problem raised was anxiety. Plasticine play therapy was carried out on one child using the Facial Anxiety Scale (FAS) instrument with 3 days of plasticine play therapy from April 30-May 2, 2024 in a day 1 meeting for 10-15 minutes with the results of anxiety resolved on a scale of 2 (no anxiety). This study obtained data that there was a decrease in anxiety levels in An. R age 6 years from a score of 4 (moderate anxiety) to a score of 2 (no anxiety). Plasticine play therapy in preschoolers (3-6 years) due to hospitalization of anxiety can help in reducing anxiety.